2008
DOI: 10.1007/s11365-008-0090-3
|View full text |Cite
|
Sign up to set email alerts
|

Human capital and sustainable competitive advantage: an analysis of the relationship between training and performance

Abstract: This article analyses the importance of training as a creator of human capital, which enables a company to obtain competitive advantages that are sustainable in the long-term that result in greater profitability. The study is based on the general theoretical framework of resource and capacity theory. The study not only analyses the impact of the influence of training on performance; it also attempts to analyse the nature of such a relationship in greater depth. This being the case, an attempt has been made to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(3 citation statements)
references
References 71 publications
0
3
0
Order By: Relevance
“…Human capital resources containing education, training and experience are regarded as critical for creating a firm's competitiveness and value (Barney, 1991;Saridakis et al, 2017). Del Valle and Castillo (2009) suggested training as an investment in human capital, which helps enterprises acquire a competitive advantage that results in higher profitability. A firms'-human capital can be defined as a profitability factor (Blundell et al, 1999) and helps to absorb new knowledge, technology and skills (Unger et al, 2011;Reuber & Fisher, 1999).…”
Section: Investment In Human Capital and Performancementioning
confidence: 99%
“…Human capital resources containing education, training and experience are regarded as critical for creating a firm's competitiveness and value (Barney, 1991;Saridakis et al, 2017). Del Valle and Castillo (2009) suggested training as an investment in human capital, which helps enterprises acquire a competitive advantage that results in higher profitability. A firms'-human capital can be defined as a profitability factor (Blundell et al, 1999) and helps to absorb new knowledge, technology and skills (Unger et al, 2011;Reuber & Fisher, 1999).…”
Section: Investment In Human Capital and Performancementioning
confidence: 99%
“…Among these intangible resources, human capital plays a determining role in building a sustainable economy. Societies replacing women or not using them to their fullest capacity does not serve this goal [37].…”
Section: Discussionmentioning
confidence: 99%
“…Further, Shrivastava and Shaw () showed that close linkages between technology and human resources can offer competitive advantage. Both Danvila‐del‐Valle and Castillo () and Heneman et al () proposed that researchers should develop theories specific to small firms as HRM knowledge and experience has been derived mostly from research conducted in large firms. Using theory inappropriate to the context can lead to misunderstandings.…”
mentioning
confidence: 99%